ANALYSIS OF THE DETERMINANTS OF THE BANKING INDUSTRY PROFITABILITY IN INDONESIA (EMPIRICAL STUDY 2003 – 2011) - Muhammad Sobarsyah; Abdul Rahman Kadir; Temi Alriady (Journal of Business Issues, 2023)
The purposes of this banking industry study are 1) to analyze the effect of macroeconomic conditions that represented by gross domestic product and inflation, and the effect of loan to deposit ratio on earning assets commercial bank; 2) to analyze the effect earning assets, non performing loans, interest rate of working capital loan and operational cost on profitability of commercial bank in Indonesia; 3) to explain about the growth of banking industry and their role as financial intermediary institution after monetary and economic crisis. This study use the quantitative method by multiple regression model to analyze time series data of commercial bank in Indonesia. The results of that multiple regression model indicated gross domestic product, previously earning assets and loan to deposit ratio have positive and significant effect to commercial bank earning assets. Meanwhile, inflation has not significant effect to commercial bank earning assets. Then, earning assets, previously profit and interest rate of working capital loan have positive and significant effect to commercial bank profit, but both of non performing loans and operational cost have significant inverse relationship to commercial bank profit. This results show that banking industry more concern to retain the profitability by expand their businnes than to provide cost efficiency. According to this study, in order to retain banking industry performance are developing economic growth that condusive to increase financial intermediary of banking industry, improving cost efficiency to provide competition which lower lending interest rate, and extending financial service area to reach micro and small enterprises as a part of financial inclusion strategy.